2021
DOI: 10.1177/13591053211017198
|View full text |Cite
|
Sign up to set email alerts
|

The meaning of loneliness to stroke survivors: A qualitative study in Northeast England

Abstract: This study explored stroke survivors’ experiences of loneliness. Drawing on interviews with 29 community-dwelling stroke survivors living in the Northeast of England, we found several themes: loneliness as being alone, the season or time, lack of understanding from those without any experience of stroke, reduced autonomy, and deterioration of social relations. It is important that healthcare professionals pay attention to the aspects of life that may increase the chances of a stroke survivor becoming lonely af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Loneliness has been defined as ‘a subjective feeling of the absence of a social network or a companion’ and has been negatively associated with cardiovascular and mental health outcomes [60]. In cancer survivors [61], stroke survivors [62] and diabetes [63], loneliness has impacted health outcomes negatively. We found that reducing loneliness was related to the reflection on challenges prompted by the reflection sheets both individually and in groups.…”
Section: Discussionmentioning
confidence: 99%
“…Loneliness has been defined as ‘a subjective feeling of the absence of a social network or a companion’ and has been negatively associated with cardiovascular and mental health outcomes [60]. In cancer survivors [61], stroke survivors [62] and diabetes [63], loneliness has impacted health outcomes negatively. We found that reducing loneliness was related to the reflection on challenges prompted by the reflection sheets both individually and in groups.…”
Section: Discussionmentioning
confidence: 99%
“…Loneliness has mainly been studied in older patients (Poscia et al, 2018), but stroke survivors also experience it (Byrne et al, 2022). Additionally, people with strokes experience similar levels of loneliness as older subjects do, owing to the loss of their social role (Yang et al, 2021). Intervention programs with a storytelling aspect can have a positive effect on emotions and loneliness in people with stroke (Alawafi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The qualitative data support this theory, but this was not reflected in participants loneliness measured by the DJG (M = 3.60, SD = 1.13) which would not indicate such a ceiling effect. Whilst measures of loneliness are useful for capturing some "universal" features of loneliness, there have previously been questions arising with how well they relate to the experiences of non-neurotypical populations (Yang et al, 2021). Therefore, our survivors' phenomenological experiences of loneliness may differ to their quantification of these experiences.…”
Section: Discussionmentioning
confidence: 99%